2019
DOI: 10.1016/j.engstruct.2019.109625
|View full text |Cite
|
Sign up to set email alerts
|

Influence of time-dependent material degradation on life cycle serviceability of interspersed railway tracks due to moving train loads

Abstract: Presently, timber-sleepered tracks are still being adopted in railway networks transporting goods and passengers. However, the deterioration of timber sleepers is evident after years of service due to natural decay; and it is difficult to seek cost-effective hardwood sleepers to replace the aging sleepers. An impermanent "interspersed" approach is an alternative method used to substitute rotten timbers with concrete sleepers. Although the interspersed tracks offer a cost-effective short-term solution for certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…As can be seen from Figure 12, changing the modulus of elasticity has limited influence on the dynamic factors, ranging from 2.8 to 3.0. A similar finding could be reached for contact forces [51,52]. (Figure 12b) By contrast, the maximum bending moment distributions along a turnout are affected by different moduli of elasticity.…”
Section: Effects Of Sleeper Stiffnesssupporting
confidence: 78%
“…As can be seen from Figure 12, changing the modulus of elasticity has limited influence on the dynamic factors, ranging from 2.8 to 3.0. A similar finding could be reached for contact forces [51,52]. (Figure 12b) By contrast, the maximum bending moment distributions along a turnout are affected by different moduli of elasticity.…”
Section: Effects Of Sleeper Stiffnesssupporting
confidence: 78%
“…The models used in this study were previously used to analyse the vertical responses of interspersed tracks under moving train loads. The results were validated using experimental parameters, field data, and previous laboratory results [18][19][20][21][22]. However, interspersed railway track buckling has never been investigated, so the validation of a plain concrete sleeper track was considered.…”
Section: Model Validationmentioning
confidence: 97%
“…Moving train loads were applied to interspersed tracks to study the vertical dynamic responses. It was observed that the replacement of timber sleepers by concrete tends to increase the deterioration rate of the railway track, as uplift behaviour occurs [21]. The condition of deteriorated interspersed track is presented in Figure 1.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to open literature and industry knowledge, this practice could consequently undermine the existing ground foundations and also induce inconsistent local stiffness problems in the rail track system [13,[15][16][17] and in addition to different track decay rates [18][19][20][21][22][23][24][25]. Studies of interspersed tracks have been carried out [26][27][28][29] and it has been found that the replacement of timber sleepers by concrete possibly increase the deterioration rate of the railway track, as uplift behaviour occurs [29].…”
Section: Introductionmentioning
confidence: 99%